NiO / Ag / ZnIn2S4 heterojunction nanosheet array and preparation method thereof and room temperature gas sensor

By designing the NiO/Ag/ZnIn2S4 heterojunction nanosheet array with S-type sandwich structure, the problems of high photogenerated carrier recombination rate and low visible light absorption efficiency in photoexcited semiconductor gas sensors are solved, and high sensitivity and high selectivity detection of triethylamine gas at room temperature are achieved.

CN119349655BActive Publication Date: 2025-04-18JIANGXI NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411934423.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-18
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing semiconductor gas-sensitive materials have high photogenerated carrier recombination rate and low visible light absorption efficiency under photoexcitation, which limits the performance improvement of photoexcited semiconductor gas sensors.

Method used

A NiO/Ag/ZnIn2S4 heterojunction nanosheet array with an S-type sandwich structure was designed, and a ternary heterojunction was constructed by introducing precious metal Ag between two semiconductor components of the S-type heterojunction to promote photogenerated carrier separation and enhance visible light absorption.

Benefits of technology

High sensitivity and selective detection of triethylamine gas at room temperature is achieved, showing a response to 100 ppm triethylamine up to 30, with excellent selectivity and low detection limits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349655B_ABST
    Figure CN119349655B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nanomaterial heterojunction, and specifically relates to NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet array and preparation method thereof and room temperature gas sensor. The heterojunction nanosheet array comprises a substrate and NiO / Ag / ZnIn grown in situ on the surface of the substrate. 2 S 4 Heterojunction nanosheet arrays; NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays are composed of NiO porous nanosheets, Ag nanoparticles and ZnIn 2 S 4 The nanosheets are composed of NiO nanosheets, in which the NiO nanosheets are in a vertically staggered array structure, the Ag nanoparticles are evenly dispersed on the surface of the NiO porous nanosheets, and the ZnIn 2 S 4 The nanosheets wrap around the NiO porous nanosheets. The preparation process of the present invention is simple, the cost is low, and the NiO / Ag / ZnIn 2 S 4 The heterojunction nanosheet array has good heterojunction interface contact, and the presence of Ag nanoparticles promotes the bonding of NiO and ZnIn 2 S 4 Electron transfer between ZnIn 2 S 4 The wrapping increases the specific surface area of ​​the material. NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays can be used in room-temperature gas sensors, specifically for room-temperature highly selective detection of triethylamine under white light excitation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material heterojunction, and specifically relates to a NiO / Ag / ZnIn2S4 heterojunction nanosheet array and a preparation method thereof and a room temperature gas sensor. Background Art

[0002] Semiconductor gas sensors based on metal oxides can effectively detect and monitor environmental gases. However, traditional semiconductor gas sensors generally need to be heated and driven at high temperatures to work, which greatly increases the power consumption of the sensor and the risk of using it in flammable and explosive atmospheres. The excitation of semiconductor gas-sensitive materials by photons can enhance the gas-sensitive response of semiconductor materials by generating abundant photogenerated carriers and surface reactive species. This method has been shown to be promising to replace traditional thermal excitation and significantly reduce the operating temperature of the sensor. However, the extremely high photogenerated carrier recombination rate and low visible light absorption efficiency of common semiconductor gas-sensitive materials greatly limit the improvement of gas-sensitive performance under photoexcitation, which has become the two major bottlenecks for the further development of photoexcitation semiconductor gas sensors.

[0003] Designing semiconductor heterojunctions is the most common strategy to solve the problem of high recombination rate of photogenerated carriers in semiconductor gas-sensitive materials. Compared with the three traditional types of semiconductor heterojunctions, the new S-type heterojunction discovered in recent years has enhanced photogenerated carrier separation efficiency due to its unique photogenerated carrier transfer mechanism, while maintaining the oxidation / reduction ability of photogenerated carriers to the maximum extent. The unique advantages of the S-type heterojunction have led to a large number of studies in the field of photocatalysis (including photocatalytic hydrogen production, degradation of water pollutants, carbon dioxide reduction, etc.) in recent years. However, so far, research on S-type heterojunctions in the field of semiconductor gas sensors has received little attention. The unique advantages of the S-type heterojunction are very likely to solve the problem of high recombination rate of photogenerated carriers in photoexcited semiconductor gas sensors. In addition, the problem of low visible light absorption efficiency of semiconductor gas-sensitive materials can be largely solved by reasonably selecting narrow-bandgap semiconductor components with good visible light absorption effect in the S-type heterojunction to replace traditional wide-bandgap semiconductor gas-sensitive materials (such as ZnO, SnO2 and TiO2). In conclusion, there is an urgent need to experimentally develop novel S-type heterojunctions for use in the field of photoexcited semiconductor gas sensors.

[0004] For the S-type heterojunction constructed by directly compounding two semiconductors, recent studies have found that the competition of directional migrating carriers and the unstable contact interface caused by lattice structure mismatch often pose great challenges to the effective separation of photogenerated carriers at the interface. Therefore, it is urgent to solve this problem, which is expected to further accelerate the development of light-excited semiconductor gas sensors. Summary of the invention

[0005] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a NiO / Ag / ZnIn2S4 heterojunction nanosheet array and its preparation method and application, specifically an S-type sandwich structure NiO / Ag / ZnIn2S4 heterojunction nanosheet array and its preparation method and room temperature gas sensor.

[0006] In order to solve the competition of directional migration carriers in the S-type heterojunction of the direct composite structure of two semiconductors and the unstable contact interface problem caused by lattice structure mismatch, the applicant has found through research that if a noble metal is introduced between the two semiconductor components of the S-type heterojunction to construct a sandwich-type ternary heterojunction, this problem can be well solved. On the one hand, noble metals can act as electron traps and media, greatly promoting the efficient separation of photogenerated carriers at the interface. On the other hand, the surface plasmon resonance (SPR) effect of noble metals can further enhance the absorption of visible light by semiconductor materials and promote the generation of photogenerated carriers. In short, the introduction of noble metals in S-type heterojunctions is expected to further accelerate the development of photoexcited semiconductor gas sensors.

[0007] In the present invention, the applicant has designed a novel sandwich NiO / Ag / ZnIn2S4 ternary S-type heterojunction nanosheet array. The heterojunction is composed of a nickel oxide porous nanosheet array grown in situ on the surface of a commercial alumina gas-sensitive substrate, an Ag nanoparticle intermediate layer, and a two-dimensional ultra-thin ZnIn2S4 nanosheet wrapped on the outermost surface. Thanks to the synergistic effect of the unique photogenerated carrier transfer mechanism of the S-type heterojunction, the SPR effect of the precious metal Ag nanoparticles, and the design of the porous nanoarray structure, the sensor can achieve high sensitivity and high selectivity detection of triethylamine gas at room temperature under the excitation of low-power white LED light (0.06W), showing a response of up to 30 (R g / R a ), while having excellent selectivity and a low detection limit (LOD) of 447 ppb. Importantly, the sandwich NiO / Ag / ZnIn2S4 nanoarray is in-situ grown on the surface of a commercial alumina gas-sensitive substrate, which greatly simplifies the complex manufacturing process of traditional semiconductor gas sensors (including powder synthesis, slurry preparation, slurry coating, thick film drying, etc.), while effectively avoiding a series of problems in the film formation process of semiconductor materials, including agglomeration, structural damage and insufficient electrical contact. Based on the first-principles calculations and spectroscopic characterization of the system (including in-situ infrared), the applicant conducted an in-depth study of the gas-sensing mechanism of this ternary S-type heterojunction. This study provides a new idea for synergistically improving the gas-sensing performance of photoexcited semiconductor gas sensors through the S-type mechanism and the noble metal SPR effect, and will provide important experimental and theoretical guidance for the material design of photoexcited semiconductor gas sensors.

[0008] The technical solution of the present invention is as follows:

[0009] A first aspect of the present invention provides a NiO / Ag / ZnIn2S4 heterojunction nanosheet array, comprising a substrate and a NiO / Ag / ZnIn2S4 heterojunction nanosheet array in-situ grown on the surface of the substrate, wherein the NiO / Ag / ZnIn2S4 heterojunction array is composed of NiO porous nanosheets, Ag nanoparticles and ZnIn2S4 nanosheets;

[0010] The NiO porous nanosheets are in a vertically staggered array structure, the Ag nanoparticles are evenly dispersed on the surface of the NiO porous nanosheets, and the ZnIn2S4 wraps the NiO porous nanosheets.

[0011] The present invention constructs a semiconductor gas sensor array in situ on a gas-sensitive substrate. Since the sensing layer is an array constructed in situ on the gas-sensitive substrate, this not only avoids a series of problems caused by the thick film formation process in the traditional process, but also greatly simplifies the manufacturing cost of the device and makes the miniaturization of the device possible. In addition, due to the close combination between the sensing film and the gas-sensitive substrate, the consistency and reliability of the sensor are also guaranteed. Most importantly, since the sensor array is usually porous and has a large specific surface area, this is very conducive to the diffusion of the target gas and the surface gas sensor reaction.

[0012] As a further preferred embodiment, the substrate is an Al2O3 gas sensitive substrate.

[0013] The Al2O3 gas-sensitive substrate is a commercially available flat Al2O3 gas-sensitive substrate. The substrate is made of cheap and readily available Al2O3, and has two pairs of Pt interdigital electrodes on the surface, one pair of which is a heating electrode and the other pair is a resistance signal collection electrode. Substrate heating and resistance signal collection are very convenient, and the two pairs of electrodes do not interfere with each other. NiO / Ag / ZnIn2S4 heterojunction nanosheet array is used as a new type of gas-sensitive sensing layer for surface gas adsorption and gas-sensitive reaction.

[0014] As a further preferred embodiment, the lateral size of the NiO porous nanosheet is 50 nm to 150 nm, the size of the Ag nanoparticle is 1 nm to 20 nm, and the thickness of the ZnIn2S4 nanosheet package is 10 nm to 50 nm.

[0015] As a further preferred embodiment, the loading amount of the Ag nanoparticles is 2 wt% to 3 wt%;

[0016] The specific surface area of ​​NiO / Ag / ZnIn2S4 is 90m2 / g~100m 2 / g.

[0017] The second aspect of the present invention provides a method for preparing the NiO / Ag / ZnIn2S4 heterojunction nanosheet array, comprising the following steps:

[0018] A NiO porous nanosheet is grown on the surface of a substrate by a hydrothermal method combined with an annealing treatment, wherein the NiO porous nanosheet is a vertically staggered growth array structure;

[0019] Modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition to obtain an intermediate product NiO / Ag nanosheet array;

[0020] A water bath method is used to grow ZnIn2S4 nanosheets on the surface of the NiO / Ag nanosheet array to obtain a final product, a NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

[0021] As a further preferred embodiment, the step of growing NiO porous nanosheets on the substrate surface by a hydrothermal method combined with annealing treatment specifically includes:

[0022] Nickel nitrate, ammonium fluoride and urea are dissolved in water and stirred to obtain a reaction solution. Then, a substrate is added to the reaction solution for a hydrothermal reaction. The reaction time is 4 h~9 h and the reaction temperature is 80 ℃~120 ℃. After the reaction, the substrate is washed, dried and then annealed. The annealing temperature is 450 ℃~650 ℃ and the annealing time is 1 h~3 h. After the annealing treatment, NiO porous nanosheets are obtained.

[0023] When the reaction temperature is 100 ℃ ~ 150 ℃, the alkaline source urea begins to decompose slowly. If the temperature is too low, urea cannot decompose to produce OH - , Ni(OH)2 cannot nucleate and grow; if the temperature is too high, urea decomposes too quickly, and ammonium fluoride cannot adjust the pH value of the reaction system through buffering effect; when the annealing temperature is 450 ℃ ~ 600 ℃, the purpose of annealing treatment is to convert Ni(OH)2 into NiO. This process mainly involves decomposition and dehydration. If the temperature is too low, Ni(OH)2 cannot be completely decomposed and dehydrated into NiO; if the temperature is too high, NiO nanosheets will continue to grow, causing the nanosheets to become thicker and sticky.

[0024] As a further preferred embodiment, the molar ratio of nickel nitrate, ammonium fluoride and urea is 1:3-5:5-7. Urea is an alkali source, and its decomposition can produce OH - , the metal Ni ions and OH in nickel nitrate -Combined to form Ni(OH)2. As a strong acid and weak base salt, ammonium fluoride can effectively regulate the pH value of the reaction system, thereby controlling the nucleation and growth of Ni(OH)2, and then forming an ultra-thin nanosheet morphology. Through a large number of experimental studies, it was found that the optimal molar ratio of nickel nitrate, ammonium fluoride and urea is 1:4:5. Too much or too little urea and ammonium fluoride are not conducive to the formation of the optimal nanosheet structure.

[0025] As a further preferred embodiment, modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition specifically comprises the following steps:

[0026] Pour the silver nitrate solution into water and mix well to obtain a mixed solution;

[0027] The NiO porous nanosheet is immersed in the mixed solution to perform a photodeposition reaction, and a mercury lamp is used to irradiate the NiO porous nanosheet. After the reaction is completed, the NiO porous nanosheet is washed and dried to obtain a NiO / Ag nanosheet array.

[0028] As a further preferred embodiment, the power of the mercury lamp is 600 W to 1200 W, and the irradiation time is 0.1 h to 1.5 h;

[0029] The molar ratio of silver nitrate to nickel oxide is 1:200-400; more preferably, the optimal molar ratio of silver nitrate to nickel oxide is 1:400.

[0030] As a further preferred embodiment, growing ZnIn2S4 nanosheets on the surface of the NiO / Ag nanosheet array by a water bath method specifically comprises the following steps:

[0031] Adjust the pH value of water to 1-3 with nitric acid, add glycerol, and ultrasonicate to obtain a solution;

[0032] Zinc chloride, indium chloride and thioacetamide are dissolved in the solution, mixed and stirred to obtain a reaction solution, and then the NiO / Ag porous nanosheet is immersed in the reaction solution for a water bath reaction, the temperature is maintained at 20°C~100°C, and the reaction is carried out for 1 h~4 h. After the reaction is completed, the product is washed and dried to finally obtain a NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

[0033] As a further preferred embodiment, the concentration of the nitric acid is 0.5 mol / L to 2 mol / L, and the volume ratio of the glycerol to water is 1 to 3:15 to 35;

[0034] The molar ratio of the zinc chloride, indium chloride and thioacetamide is 1:1-3:2-5.

[0035] A third aspect of the present invention provides a room temperature gas sensor comprising the above-mentioned NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

[0036] As a further preferred embodiment, the room temperature gas sensor is a gas sensor for detecting triethylamine.

[0037] The NiO / Ag / ZnIn2S4 heterojunction nanosheet array of the present invention is applied to a room temperature gas sensor and has high selectivity for detecting triethylamine at room temperature under white light excitation.

[0038] The present invention has at least one of the following beneficial effects:

[0039] The preparation process of the present invention is simple and the cost is low. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared by the present invention has good heterogeneous interface contact, and the presence of Ag nanoparticles in the NiO / Ag / ZnIn2S4 heterojunction nanosheet array greatly promotes the electron transfer between NiO and ZnIn2S4, and the wrapping of ZnIn2S4 increases the specific surface area of ​​the material. In addition, the NiO / Ag / ZnIn2S4 heterojunction nanosheet array can be used in room temperature gas sensors, specifically in room temperature high-selective detection of triethylamine under white light excitation. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Shown are X-ray diffraction (XRD) patterns of the NiO / Ag / ZnIn2S4 heterojunction nanosheet arrays, the comparative sample, pure NiO, and pure ZnIn2S4 prepared in Example 1;

[0041] Figure 2 The figures show scanning electron microscope (SEM) images, transmission electron microscope (TEM) images and element distribution maps of the NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared in Example 1 and the comparative sample NiO; wherein, (a) and (b) are SEM images of the NiO nanosheet array at different resolutions; (c) and (d) are TEM morphology images of NiO / Ag at different resolutions; (e) and (f) are morphology characterizations of NiO / ZnIn2S4 at different resolutions; (g) and (h) are SEM characterizations of NiO / Ag / ZnIn2S4 at different resolutions; (i), (j) and (k) are TEM images and high-resolution TEM images of NiO / Ag / ZnIn2S4 at different resolutions; (l), (m), (n), (o), (p), (q) and (r) are element mapping images of NiO / Ag / ZnIn2S4;

[0042] Figure 3Shown are the nitrogen adsorption / desorption isotherms and corresponding pore size distribution curves of the NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared in Example 1 and the comparative sample; wherein, (a) NiO; (b) NiO / Ag; (c) NiO / ZnIn2S4; (d) NiO / Ag / ZnIn2S4.

[0043] Figure 4 Shown are the x-ray photoelectron spectroscopy (XPS) graphs of the NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared in Example 1 and the comparative sample; wherein, (a) XPS spectrum graph of the Ni element; (b) XPS spectrum graph of the O element; (c) XPS spectrum graph of the Ag element; (d) XPS spectrum graph of the Zn element; (e) XPS spectrum graph of the In element; and (f) XPS spectrum graph of the S element.

[0044] Figure 5 Shown are the in situ x-ray photoelectron spectroscopy (in situ XPS) images of the NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared in Example 1 and the comparative sample; among them, (a) the peak position shift of the O element; (b) the peak position shift of the Zn element; (c) the peak position shift of the In element; and (d) the peak position shift of the S element.

[0045] Figure 6 Shown are the kinetic gas-sensitive responses of the NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared in Example 1 and the comparative sample to 100 ppm triethylamine under room temperature white light conditions; wherein, (a) NiO / Ag / ZnIn2S4; (b) NiO / ZnIn2S4; (c) NiO / Ag; (d) NiO.

[0046] Figure 7 Shown are the kinetic gas-sensitive responses of the NiO / Ag / ZnIn2S4 heterojunction nanosheet array prepared in Example 1 and the comparative sample to different concentrations of triethylamine under room temperature white light conditions; among them, (a) NiO / Ag / ZnIn2S4; (b) NiO / ZnIn2S4; (c) NiO / Ag; (d) NiO. DETAILED DESCRIPTION

[0047] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] Example 1

[0049] A NiO / Ag / ZnIn2S4 heterojunction nanosheet array, the preparation method of which comprises the following steps:

[0050] Step 1: First, wash the commercial flat Al2O3 gas-sensitive substrate (produced by Wuhan Huachuang Ruike Technology Co., Ltd.) repeatedly in deionized water and anhydrous ethanol and dry it for later use;

[0051] Step 2: Add nickel nitrate (Ni(NO3)2·6H2O), ammonium fluoride (NH4F) and urea (CH4N2O) in a molar ratio of 1:4:5 into a polytetrafluoroethylene autoclave, then add deionized water until the inner volume filling degree is 72%, and continue magnetic stirring for 0.2 hours to obtain a reaction solution; add the washed commercial flat Al2O3 gas-sensitive substrate to the reaction solution and perform a hydrothermal reaction, setting the reaction temperature to 100 °C and the reaction time to 8 hours; after the reaction, wash and dry the commercial flat Al2O3 gas-sensitive substrate, and then anneal it in a muffle furnace, setting the annealing temperature to 500 °C and the annealing time to 2 hours to obtain a NiO porous nanosheet array;

[0052] Step 3: Pour silver nitrate (AgNO3) solution (0.01 mmol) into 40 mL of deionized water and mix well to obtain a mixed solution; then immerse the NiO porous nanosheet array in the mixed solution for photodeposition reaction, set the power of the mercury lamp to 1000 W to irradiate the NiO porous nanosheet array, and the reaction time is 30 minutes. After the reaction, wash and dry the NiO porous nanosheet array to obtain a NiO / Ag porous nanosheet array.

[0053] Step 4: Adjust the pH value of deionized water (20 mL) to 2.5 with 1 mol / L nitric acid, add 3 mL glycerol, and ultrasonicate for 1 hour. Dissolve zinc chloride, indium chloride, and thioacetamide in the above solution at a molar ratio of 1:1:2, mix well, and stir for 1 hour to obtain a reaction solution, then immerse the NiO / Ag porous nanosheet array in the reaction solution for water bath reaction, and use a water bath to maintain the temperature of the reaction solution at 80°C for 2 hours. After the reaction, wash the NiO / Ag / ZnIn2S4 heterojunction nanosheet array and dry it to finally obtain the NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

[0054] Example 2

[0055] A NiO / Ag / ZnIn2S4 heterojunction nanosheet array, the preparation method of which comprises the following steps:

[0056] Step 1: First, wash the commercial flat Al2O3 gas-sensitive substrate (produced by Wuhan Huachuang Ruike Technology Co., Ltd.) repeatedly in deionized water and anhydrous ethanol and dry it for later use;

[0057] Step 2: Add nickel nitrate (Ni(NO3)2·6H2O), ammonium fluoride (NH4F) and urea (CH4N2O) in a molar ratio of 1:4:6 into a polytetrafluoroethylene autoclave, then add deionized water until the inner volume filling degree is 65%, and continue magnetic stirring for 0.5 hours to obtain a reaction solution; add the washed commercial flat Al2O3 gas-sensitive substrate to the reaction solution and perform a hydrothermal reaction, setting the reaction temperature to 110 °C and the reaction time to 10 hours; after the reaction, wash and dry the commercial flat Al2O3 gas-sensitive substrate, and then anneal it in a muffle furnace, setting the annealing temperature to 400 °C and the annealing time to 2 hours to obtain a NiO porous nanosheet array;

[0058] Step 3: Pour silver nitrate (AgNO3) solution (0.02 mmol) into 50 mL of deionized water and mix well to obtain a mixed solution; then immerse the NiO porous nanosheet array in the mixed solution for photodeposition reaction, set the power of the mercury lamp to 800 W to irradiate the NiO porous nanosheet array, and the reaction time is 45 minutes. After the reaction, wash and dry the NiO porous nanosheet array to obtain a NiO / Ag porous nanosheet array.

[0059] Step 4: Adjust the pH value of deionized water (35 mL) to 3.0 with 2.5 mol / L nitric acid, add 1 mL glycerol, and ultrasonicate for 1 hour. Dissolve zinc chloride, indium chloride, and thioacetamide in the above solution at a molar ratio of 1:2:2, mix well, and stir for 1 hour to obtain a reaction solution, then immerse the NiO / Ag porous nanosheet array in the reaction solution for water bath reaction, maintain the temperature of the reaction solution at 100°C in a water bath, and react for 1.5 hours. After the reaction, wash the NiO / Ag / ZnIn2S4 heterojunction nanosheet array and dry it to finally obtain the NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

[0060] Example 3

[0061] A NiO / Ag / ZnIn2S4 heterojunction nanosheet array, the preparation method of which comprises the following steps:

[0062] Step 1: First, wash the commercial flat Al2O3 gas-sensitive substrate (produced by Wuhan Huachuang Ruike Technology Co., Ltd.) repeatedly in deionized water and anhydrous ethanol and dry it for later use;

[0063] Step 2: Add nickel nitrate (Ni(NO3)2·6H2O), ammonium fluoride (NH4F) and urea (CH4N2O) in a molar ratio of 1:4:5 into a polytetrafluoroethylene autoclave, then add deionized water until the inner volume filling degree is 80%, and continue magnetic stirring for 1 hour to obtain a reaction solution; add the washed commercial flat Al2O3 gas-sensitive substrate to the reaction solution and perform a hydrothermal reaction, set the reaction temperature to 80 °C, and the reaction time to 15 hours; after the reaction, wash and dry the commercial flat Al2O3 gas-sensitive substrate, and then anneal it in a muffle furnace, set the annealing temperature to 550 °C, and the annealing time to 2 hours to obtain a NiO porous nanosheet array;

[0064] Step 3: Pour silver nitrate (AgNO3) solution (0.03 mmol) into 35 mL of deionized water and mix well. Then immerse the NiO porous nanosheet array into the mixed solution for photodeposition reaction. Set the power of the mercury lamp to 1100 W to irradiate the NiO porous nanosheet array. The reaction time is 25 minutes. After the reaction, wash and dry the NiO porous nanosheet array to obtain a NiO / Ag porous nanosheet array.

[0065] Step 4. Adjust the pH value of deionized water (15 mL) to 2.0 with 2 mol / L nitric acid, add 5 mL glycerol, and ultrasonicate for 0.5 hours. Dissolve zinc chloride, indium chloride, and thioacetamide in the above solution at a molar ratio of 1:3:4, mix well, and stir for 1 hour to obtain a reaction solution, then immerse the NiO / Ag porous nanosheet array in the reaction solution for water bath reaction, maintain the temperature of the reaction solution at 130°C in a water bath, and react for 2 hours. After the reaction, wash the NiO / Ag / ZnIn2S4 heterojunction nanosheet array and dry it to finally obtain the NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

[0066] Comparative Example 1

[0067] Only NiO nanosheets are prepared, and the preparation method is as follows:

[0068] Nickel nitrate (Ni(NO3)2·6H2O), ammonium fluoride (NH4F) and urea (CH4N2O) were added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat Al2O3 gas-sensitive substrate was added to the reaction solution and a hydrothermal reaction was carried out, and the reaction temperature was set at 100 ℃ and the reaction time was set to 8 hours; after the reaction, the commercial flat Al2O3 gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace, and the annealing temperature was set at 500 ℃ and the annealing time was set to 2 hours to obtain a NiO nanosheet array.

[0069] Comparative Example 2

[0070] Only NiO / Ag porous nanosheet arrays are prepared, and the preparation method is as follows:

[0071] Nickel nitrate (Ni(NO3)2·6H2O), ammonium fluoride (NH4F) and urea (CH4N2O) were added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat Al2O3 gas-sensitive substrate was added to the reaction solution and a hydrothermal reaction was carried out, and the reaction temperature was set at 100 ℃ and the reaction time was set to 8 hours; after the reaction, the commercial flat Al2O3 gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace, and the annealing temperature was set at 500 ℃ and the annealing time was set to 2 hours to obtain a NiO porous nanosheet array.

[0072] Silver nitrate (AgNO3) solution (0.01 mmol) was poured into 40 mL of deionized water and mixed to obtain a mixed solution. The NiO porous nanosheet array was then immersed in the mixed solution for photodeposition reaction. The power of the mercury lamp was set to 1000 W to irradiate the NiO porous nanosheet array for 30 minutes. After the reaction, the NiO porous nanosheet array was washed and dried to obtain a NiO / Ag nanosheet array.

[0073] Comparative Example 3

[0074] Only NiO / ZnIn2S4 material is prepared, and the preparation method is as follows:

[0075] Nickel nitrate (Ni(NO3)2·6H2O), ammonium fluoride (NH4F) and urea (CH4N2O) were added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat Al2O3 gas-sensitive substrate was added to the reaction solution and a hydrothermal reaction was carried out, and the reaction temperature was set at 100 ℃ and the reaction time was set to 8 hours; after the reaction, the commercial flat Al2O3 gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace, and the annealing temperature was set at 500 ℃ and the annealing time was set to 2 hours to obtain a NiO porous nanosheet array.

[0076] The pH value of the water was adjusted to 2.5 with 1 mol / L nitric acid, 3 mL glycerol was added, and ultrasonication was performed for 0.5 hours. Zinc chloride, indium chloride and thioacetamide were dissolved in the above solution at a molar ratio of 1:1:2, mixed, and stirred for 1 hour to obtain a reaction solution, and then the NiO porous nanosheet array was immersed in the reaction solution for a water bath reaction, and the temperature of the reaction solution was maintained at 80°C in a water bath pot for 2 hours. After the reaction, the NiO / ZnIn2S4 heterojunction nanosheet array was washed and dried to finally obtain the NiO / ZnIn2S4 heterojunction nanosheet array.

[0077] Figure 1 The X-ray diffraction (XRD) patterns of the NiO / Ag / ZnIn2S4 heterojunction array in Example 1 and the comparative sample NiO nanosheet (Comparative Example 1), NiO / Ag porous nanosheet array (Comparative Example 2), NiO / ZnIn2S4 material (Comparative Example 3), pure phase NiO and pure phase ZnIn2S4 are shown in FIG. 47-1049 of the Joint Committee on Powder Diffraction Standards for the XRD pattern of pure phase NiO, and JCPDS No. 65-2023 of the Joint Committee on Powder Diffraction Standards for the XRD pattern of pure phase ZnIn2S4. It can be seen that the comparative sample NiO nanosheet (Comparative Example 1) is pure phase NiO, and the NiO / Ag / ZnIn2S4 heterojunction array obtained after the composite has both NiO and ZnIn2S4 phases, which verifies the synthesis of the heterojunction. In addition, no characteristic diffraction peaks of Ag were observed in the XRD patterns of the two composite samples of NiO / Ag and NiO / Ag / ZnIn2S4, mainly due to the low loading content of Ag particles (loading amount is 2.4 wt%), and the Ag nanoparticles as an intermediate layer coated by ZnIn2S4 also largely masked their diffraction peaks.

[0078] Figure 2 The scanning electron microscope (SEM) photos, transmission electron microscope (TEM) photos and element distribution maps of the NiO / Ag / ZnIn2S4 heterojunction array in Example 1 and the comparative samples NiO, NiO / Ag and NiO / ZnIn2S4 are shown. The morphology and microstructure of the prepared samples can be observed by SEM and TEM. Figure 2 (a) and Figure 2 As shown in (b) in Figure 2, these two pictures show the morphology of NiO nanosheet arrays, which grow vertically and staggered on the surface of the gas-sensitive substrate, and the surface of the NiO nanosheets is smooth and flat, with a thickness of about 50 nanometers. Figure 2(d) in the figure is a TEM morphology photograph of the NiO / Ag sample. Since the Ag particles are small, their morphology cannot be observed in the low-magnification SEM, so TEM and high-resolution TEM (high-resolution transmission electron microscope HRTEM) are used to characterize them. From the TEM photos, it can be seen that there are a large number of evenly distributed mesopores on the surface of the nanosheets, and black Ag nanoparticles with a size of 1nm-20nm are evenly dispersed on the surface of the NiO nanosheets. With the help of HRTEM, the high-resolution lattice fringes of the particles can be clearly observed. Its crystal plane spacing is 0.241nm, which can be attributed to the (111) crystal plane of metallic Ag. Figure 2 (e) and Figure 2 (f) is the morphological characterization of NiO / ZnIn2S4. It can be observed that a large number of ZnIn2S4 nanosheets are evenly coated on the surface of NiO nanosheets, forming a good heterogeneous core-shell structure. Figure 2 (g) and Figure 2 As shown in (h), its overall morphology is not much different from NiO / ZnIn2S4. The ZnIn2S4 nanosheets uniformly wrap the NiO nanosheets and Ag nanoparticles to form a sandwich heterojunction. Figure 2 (i) Figure 2 (j) and Figure 2 (k) in the figure are the TEM image and high-resolution TEM image of NiO / Ag / ZnIn2S4, respectively. From the TEM image, it can be clearly seen that the ZnIn2S4 nanosheets cover the surface of NiO and Ag nanoparticles. The HRTEM image shows three different sets of lattice fringes. The lattice spacing of 0.241 nanometers in the upper left corner corresponds to the (111) crystal plane of Ag, the lattice spacing of 0.243 nanometers in the middle part matches the (111) crystal plane of NiO, and the 0.317 nanometers in the lower right corner is consistent with the (102) crystal plane of ZnIn2S4. The above results show that a good heterogeneous interface contact is formed between the three. In addition, Figure 2 (l) Figure 2 (m) Figure 2 (n) Figure 2 (o) in Figure 2 (p) Figure 2 (q) and Figure 2 (r) in the figure is the element mapping image of NiO / Ag / ZnIn2S4. It can be seen that the spatial distribution of Ni, O, Ag, Zn, In, and S is uniform, which is consistent with its morphological characteristics.

[0079] In order to further study the specific surface area and pore structure of the samples, the applicant tested the nitrogen adsorption-desorption isotherms of NiO, NiO / Ag, NiO / ZnIn2S4 and NiO / Ag / ZnIn2S4, such as Figure 3 As shown. All four samples show type IV isotherms and H3 hysteresis loops, indicating the presence of abundant mesopores, which is consistent with their morphological characteristics. According to calculations, the specific surface areas of NiO, NiO / Ag, NiO / ZnIn2S4 and NiO / Ag / ZnIn2S4 are 86.1123 m 2 / g, 95.5484m 2 / g, 90.3461m 2 / g and 95.7655m 2 / g. Generally speaking, a large specific surface area and porous structure will provide more active sites for gas sensing reactions, thus contributing to the improvement of performance.

[0080] The chemical composition and state of NiO, NiO / Ag, NiO / ZnIn2S4 and NiO / Ag / ZnIn2S4 were studied by measuring the x-ray photoelectron spectroscopy (XPS) spectra. Figure 4 (a) to Figure 4 (f) show the x-ray photoelectron spectroscopy (XPS) spectra of Ni, O, Ag, Zn, In and S in the four samples. Figure 4 (a) shows that for pure NiO, Ni 2p 3 / 2 The main peaks are located at 854.37 eV and 856.03 eV, respectively, and the satellite peak is located at 861.53 eV. Ni 2p 1 / 2The peaks are located at 872.01eV and 873.92 eV, respectively, and the satellite peak is located at 879.76 eV. The XPS spectra peak positions of the four samples Ni are basically the same. For the O element in Figure 4 (b), the peak at 529.88eV can be attributed to chemically adsorbed oxygen, while the O1s peak 531.62eV can be attributed to lattice oxygen. Comparing the O1s peak positions of the four samples, it can be seen that from the mono-NiO to the binary NiO / Ag and NiO / ZnIn2S4 and then to the ternary NiO / Ag / ZnIn2S4, the proportion of chemically adsorbed oxygen gradually increases, and the overall peak position moves in the direction of low binding energy, indicating that ZnIn2S4 transfers electrons to NiO, and the O element in NiO gains electrons. Figure 4 (c) is the XPS spectrum of Ag. The peak positions of Ag in the two materials can be well attributed to the peaks of metallic Ag. Figure 4 (d) - Figure 4 (f) are the peaks of the three elements Zn, In and S of ZnIn2S4, which are basically similar to those reported in the literature. The Zn 2p XPS spectrum shows two obvious peaks at 1022.0eV and 1045.1eV, and the peak position of Zn in the two samples is basically the same. However, the peaks of In and S in the ternary NiO / Ag / ZnIn2S4 are shifted to the right relative to NiO / ZnIn2S4. This is because in the process of electron transfer from ZnIn2S4 to NiO, S and In elements lose electrons, and the binding energy increases. In addition, the presence of Ag acts as a bridge for electron transfer, which greatly promotes this electron transfer process. Therefore, compared with NiO / ZnIn2S4, the peak position of the central sample NiO / Ag / ZnIn2S4 is more shifted in the direction of increasing binding energy.

[0081] In addition, if Figure 5 As shown in the figure, the peak shift of O, S and In elements in the in-situ XPS spectrum is opposite to that in the absence of light. When NiO and ZnIn2S4 are combined to form a heterojunction, the electrons of ZnIn2S4 flow to NiO with a lower Fermi level, and a built-in electric field is formed from ZnIn2S4 to NiO. Under visible light excitation, the electrons in the valence bands of NiO and ZnIn2S4 transition to the conduction band, and are transferred from NiO to ZnIn2S4 under the action of the built-in electric field. Therefore, the situation of gaining and losing electrons is exactly the opposite of the normal situation. The O element loses electrons and the binding energy increases, while the S and In elements gain electrons and the binding energy decreases. It can be confirmed that the electron transfer process of the NiO / Ag / ZnIn2S4 heterojunction conforms to the S-type separation mechanism.

[0082] On this basis, the applicant was able to detect triethylamine at room temperature using the prepared nanoarray. The responses of NiO, NiO / Ag, and NiO / ZnIn2S4 to triethylamine (100ppm) were very limited (<4), as shown in Figure 6 (b) Figure 6 (c) Figure 6 However, NiO / Ag / ZnIn2S4 exhibits excellent room temperature gas sensitivity to triethylamine under low power (0.06W) white LED light excitation. Figure 6 As shown in (a), in the eight cycles of the stability test, each time 100ppm of triethylamine was introduced, the gas sensor's response value to the target gas increased by an average of about 30 times, and eventually returned to the original response value. In the detection experiment of triethylamine at different concentrations under room temperature white light excitation, Figure 7 As shown in (a) in Figure 2, NiO / Ag / ZnIn2S4 also exhibits a gas-sensitive response to triethylamine over a wide concentration range. Figure 7 As shown in (d) in Figure 2, the gas sensing performance of NiO alone to triethylamine is low (less than 2). Figure 7 (b) and Figure 7 As shown in (c), the gas sensing performance of NiO / Ag and NiO / ZnIn2S4 to triethylamine is also low.

[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A NiO / Ag / ZnIn2S4 heterojunction nanosheet array, characterized in that: It comprises a substrate and a NiO / Ag / ZnIn2S4 heterojunction nanosheet array in-situ grown on the surface of the substrate, wherein the NiO / Ag / ZnIn2S4 heterojunction array is composed of NiO porous nanosheets, Ag nanoparticles and ZnIn2S4 nanosheets; The NiO porous nanosheet is a vertically staggered array structure, the Ag nanoparticles are evenly dispersed on the surface of the NiO porous nanosheet, and the ZnIn2S4 wraps the NiO porous nanosheet; the lateral size of the NiO porous nanosheet is 50 nm~150 nm, the size of the Ag nanoparticles is 1 nm~20 nm, and the thickness of the ZnIn2S4 nanosheet wrap is 10 nm~50 nm; the loading amount of the Ag nanoparticles is 2 wt%~3 wt%; the specific surface area of ​​the NiO / Ag / ZnIn2S4 is 90m 2 / g~100m 2 / g; The method for preparing the NiO / Ag / ZnIn2S4 heterojunction nanosheet array comprises the following steps: A NiO porous nanosheet is grown on the surface of a substrate by a hydrothermal method combined with an annealing treatment, wherein the NiO porous nanosheet is a vertically staggered growth array structure; Modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition to obtain an intermediate product NiO / Ag nanosheet array; A water bath method is used to grow ZnIn2S4 nanosheets on the surface of the NiO / Ag nanosheet array to obtain a final product, a NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

2. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 1, characterized in that: The substrate is an Al2O3 gas-sensitive substrate.

3. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 1, characterized in that: The steps of growing NiO porous nanosheets on the substrate surface by using a hydrothermal method combined with annealing treatment specifically include: Nickel nitrate, ammonium fluoride and urea are dissolved in water and stirred to obtain a reaction solution, and then a substrate is added to the reaction solution for a hydrothermal reaction, the reaction time is 4 h~9 h, the reaction temperature is 80 ℃~120 ℃, after the reaction is completed, the substrate is washed, dried, and then annealed, the annealing temperature is 450 ℃~650 ℃, the annealing time is 1 h~3 h, and after the annealing treatment, NiO porous nanosheets are obtained; Wherein, the molar ratio of the nickel nitrate, ammonium fluoride and urea is 1:3-5:5-7.

4. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 1, characterized in that: Modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition specifically comprises the following steps: Pour the silver nitrate solution into water and mix well to obtain a mixed solution; The NiO porous nanosheet is immersed in the mixed solution to perform a photodeposition reaction, and a mercury lamp is used to irradiate the NiO porous nanosheet. After the reaction is completed, the NiO porous nanosheet is washed and dried to obtain a NiO / Ag nanosheet array.

5. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 4, characterized in that: The power of the mercury lamp is 600 W to 1200 W, and the irradiation time is 0.1 h to 1.5 h; The molar ratio of the silver nitrate to the nickel oxide is 1:200-400.

6. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 1, characterized in that: The method of growing ZnIn2S4 nanosheets on the surface of the NiO / Ag nanosheet array by a water bath method specifically comprises the following steps: Adjust the pH value of water to 1-3 with nitric acid, add glycerol, and ultrasonicate to obtain a solution; Zinc chloride, indium chloride and thioacetamide are dissolved in the solution, mixed and stirred to obtain a reaction solution, and then the NiO / Ag porous nanosheet is immersed in the reaction solution for a water bath reaction, the temperature is maintained at 20°C~100°C, and the reaction is carried out for 1 h~4 h. After the reaction is completed, the product is washed and dried to finally obtain a NiO / Ag / ZnIn2S4 heterojunction nanosheet array.

7. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 6, characterized in that: The concentration of the nitric acid is 0.5 mol / L to 2 mol / L, and the volume ratio of the glycerol to water is 1 to 3:15 to 35; The molar ratio of the zinc chloride, indium chloride and thioacetamide is 1:1-3:2-5.

8. A room temperature gas sensor, characterized in that: It comprises the NiO / Ag / ZnIn2S4 heterojunction nanosheet array as described in any one of claims 1 to 2.

Citation Information

Patent Citations

  • Beta-catenin photoelectric immunoassay method based on Z-type tungsten trioxide-nanogold-indium zinc sulfide heterojunction

    CN112213499A

  • Preparation method of photocatalytic material for constructing NiO and ZnIn2S4 heterojunction based on in-situ loading

    CN116809080A

  • NiO / Bi2MoO6 heterojunction array and preparation method and application thereof

    CN117164023A